Unpacking the relationship between adolescents’ perceived school climate and negative emotions: the chain mediating roles of school belonging and social avoidance and distress - Weisong Chen; Zhen Huang; Bo Peng; Hang Hu (BMC Psychology)
Abstract Objective Guided by Self-System Processes Theory, Social Support Theory, and Stress and Coping Theory, this study investigates how perceived school climate influences adolescents’ negative emotions through the chain mediation of school belonging and social avoidance and distress. It also examines demographic differences across gender and grade and tests the structural invariance of the proposed model. Method A cross-sectional survey of 1,507 Chinese adolescents in grades 5–9 was conducted using validated scales. Independent samples t-tests and one-way ANOVA were used to examine gender and grade differences in the key variables. Structural equation modeling (SEM) tested the hypothesized mediation model, while multigroup SEM assessed structural invariance across subgroups. Results Perceived school climate reduced negative emotions both directly and indirectly, with school belonging and social avoidance and distress as key mediators. Peer support demonstrated the strongest indirect effect, while teacher support and autonomy opportunities influenced negative emotions through both direct and indirect pathways. A chain mediation pathway was identified, and structural invariance testing confirmed consistent relationships across gender and grade groups. Conclusion This study reveals a complex chain mediation mechanism and highlights the stability of structural relationships across demographic groups. The findings provide valuable theoretical and practical insights for fostering supportive school environments to promote adolescent emotional well-being.